Kondisi Stres dan Strategi Coping Stress pada Pasien Diabetes Melitus Tipe II yang Bekerja di Jakarta - Sekar Ayu Widyaningrum; Mohammad Adi Ganjar Priadi (MANASA, 2021)
Diabetes melitus type 2 is one of the non contagious chronic disease that the number of it patient continue to rise over the time in Indonesia. Fundamentally, this disease cannot be healed but could be managed to prevent complications. Patient with diabetes melitus type 2 frequently got limitations in their work such as discrimination at their workplace, risk of decreased productivity, and increased absence on their treatment. Those things are affecting to the most of the patient that have more than 45 years of age and they are on the top of their career. This research has an objective to get an overview of stress and their strategy of cope with it because stress has a major impact to their health condition. This research use qualitative approach with the purposive sampling. The characteristics of this research are patient with diabetes melitus type 2 disease, has 41 to 60 years of age who has done the self-care, and work in Jakarta. Result shows that participants suffer stress from the treatment of the disease although their performance productivity does not decrease. Participants use the strategy of combining problem focused coping mostly planful problem solving type and emotion focused coping such as seeking social support to manage their stress level.